The elderly's satisfaction with physical activity programs in senior welfare centers - Jung, Yang-Hun; Park, Jeong-Beom; Kang, Austin; Cho, Kuy-Chung (Frontiers in Public Health, 2023)
This study evaluated the exercise characteristics and satisfaction of the elderly who participated in physical activity programs provided by senior welfare centers in South Korea. We surveyed 266 participants to learn the characteristics of the elderly’s exercise participation and their satisfaction with physical activity programs in senior welfare centers. The survey was conducted from August 1 to August 31, 2022. A total of 263 copies were analyzed using the SPSS 23.0 statistical software. The top three physical activity programs that the elderly participated in senior welfare centers were dancing (25.3%), gymnastics (24.8%), and table tennis/badminton (13.2%). There were significant differences in respondents’ satisfaction according to sex, education level, spouse, family type, and monthly income per household (p<.05). The elderly were satisfied with programs (4.183 ± 0.483), facilities (3.881 ± 0.483), and instructors (3.604 ± 0.483) in order. As a result, this study presented a strategy for physical activity programs in senior welfare centers, suggesting that it is necessary to provide physical activity programs for the elderly in senior welfare centers according to their demographic and exercise characteristics.